Monatomic copper-doped porous carbon fiber as well as preparation method and application thereof

Single-atom copper-doped porous carbon fibers were prepared by electrospinning and used for the negative electrode of potassium metal battery, which solved the problem of dendrites and improved the cycle stability and cycle life of the battery.

CN119392409AActive Publication Date: 2025-02-07CENT SOUTH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411508568.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The negative electrode of potassium metal battery is prone to dendrite growth problems during the electroplating/stripping process, resulting in low Coulombic efficiency and internal short circuits, hindering its practical application.

Method used

Single-atom copper-doped porous carbon fibers were prepared by electrospinning. By immersing in a solution of 1,10-phenanthorline and silver acetate and processing at high temperature, the single-atom copper was evenly dispersed to form a three-dimensional porous structure for potassium metals. Battery negative pole.

Benefits of technology

This material has high conductivity and large specific surface area, which can effectively inhibit dendrites' growth, improve the cycle stability of potassium metal batteries, and achieve an ultra-long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392409A_ABST
    Figure CN119392409A_ABST
Patent Text Reader

Abstract

The invention discloses monatomic copper-doped porous carbon fibers as well as a preparation method and application thereof, and relates to the technical field of material preparation. The diameter of pores in the porous carbon fiber is 100-600 nm, and the specific surface area is 1000-3500 m < 2 > g <-1 >; the surface of the porous carbon fiber is doped with uniformly dispersed monatomic copper, and the content of the monatomic copper is 0.5 wt%-10.0 wt%; the preparation method comprises the following steps: adding polyvinylpyrrolidone and polytetrafluoroethylene dispersion liquid into water, stirring to form a precursor solution, preparing the precursor solution into a fiber membrane through an electrostatic spinning method, and then carrying out pre-oxidation and high-temperature carbonization on the fiber membrane to obtain the porous carbon fiber; and soaking the porous carbon fiber in a solution containing 1, 10-phenanthroline and copper acetate, drying, and performing high-temperature treatment to obtain the monatomic copper-doped porous carbon fiber. The preparation method is simple, controllable and suitable for large-scale production, and the monatomic copper-doped porous carbon fiber is applied to a potassium metal battery for the first time and has super-strong cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of material preparation, and in particular relates to single-atom copper-doped porous carbon fiber and a preparation method thereof, and application in potassium metal batteries. Background Art

[0002] As electricity develops, lithium-ion batteries are facing huge consumption demands, which raises concerns about limited resources. Therefore, alternative battery systems that utilize earth-abundant elements have become a focus of attention. For example, potassium-ion batteries are receiving widespread attention due to their comparable operating voltage and power density compared to lithium-ion batteries and their high abundance of potassium resources. To date, several types of potassium-ion battery anode materials have been developed, such as intercalation type (graphite, hard / soft carbon), conversion type (SnS 2 、MoS 2 ) and alloy type (Sn, Sb), etc. In order to achieve high specific energy of potassium batteries, potassium metal is the best choice, which has the lowest redox potential (-2.93V vs.SHE) and the highest specific capacity (687mAhg -1 ).

[0003] However, the potassium metal anode will also encounter inevitable dendrite growth problems during the electroplating / stripping process, resulting in low Coulomb efficiency, internal short circuits and other problems, which seriously hinders its practical application. Therefore, it is considered to use a conductive substrate to stabilize the potassium anode so that the potassium metal can be encapsulated in the substrate, thereby reducing the chance of side reactions, buffering volume changes, and providing a conductive network to further inhibit dendrite growth. Generally, modified metal substrates such as copper and aluminum are a type of potential substrate for stable and dendrite-free composite potassium anodes, but their high density and relatively low space utilization hinder the application of metal substrates. In contrast, carbon substrates with lower density and electrochemical stability are more advantageous for potassium accommodation, which is conducive to achieving high specific energy and energy density.

[0004] Therefore, in order to achieve high energy density and stable cycle of potassium metal batteries, we need to start from the following aspects: (1) Introducing more active sites, such as single atoms, clusters, particles, etc., can achieve low nucleation overpotential and improve potassium affinity; (2) Increasing the conductivity and specific surface area of ​​the substrate, such as porous carbon, can induce rapid ion / electron transfer, reduce local current density, and hinder dendrite growth; (3) A three-dimensional structure with sufficient internal space can effectively guide a uniform electric field and a smooth potassium coating to achieve the inhibition of dendrite growth during the cycle. Therefore, constructing a three-dimensional porous substrate material with a large number of distributed active sites is an effective solution to improve the cycle stability of potassium metal batteries.

[0005] The present invention provides a single-atom copper-doped porous carbon fiber and a preparation method thereof, and application thereof in a potassium metal battery. The porous carbon fiber with uniformly dispersed single-atom copper is prepared by electrospinning, wherein the content of the single-atom copper is 0.5wt% to 10.0wt%, the pore diameter of the porous carbon fiber is 100 to 600nm, and the specific surface area is 1000 to 3500m 2 g -1 , and the prepared single-atom copper-doped porous carbon fibers have super strong cycle stability when applied in potassium metal batteries. Summary of the invention

[0006] The purpose of the present invention is to provide single-atom copper-doped porous carbon fiber and a preparation method thereof, and application in potassium metal batteries, so as to solve the problems of inevitable dendrite growth encountered by potassium metal negative electrodes in the prior art during electroplating / stripping, resulting in low Coulomb efficiency, internal short circuit and other problems.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a single-atom copper-doped porous carbon fiber, wherein the porous carbon fiber has a three-dimensional porous structure, a pore diameter of 100 to 600 nm, and a specific surface area of ​​1000 to 3500 m 2 g -1 ;

[0009] The surface of the porous carbon fiber is doped with uniformly dispersed single-atom copper, and the content of the single-atom copper is 0.5wt% to 10.0wt%.

[0010] The second aspect of the present invention provides a method for preparing single-atom copper-doped porous carbon fiber, comprising the following steps:

[0011] (1) Preparing porous carbon fibers: adding polyvinyl pyrrolidone (PVP) and polytetrafluoroethylene dispersion (PTFE) into water and stirring to form a precursor solution, preparing a fiber membrane from the precursor solution by electrospinning, and then pre-oxidizing and carbonizing the fiber membrane at high temperature to obtain porous carbon fibers;

[0012] (2) Preparation of single-atom copper-doped porous carbon fibers: The porous carbon fibers are immersed in a solution containing 1,10-phenanthroline and copper acetate and then dried, and then treated at high temperature to obtain single-atom copper-doped porous carbon fibers.

[0013] Preferably, the precursor solution is formed in step (1), specifically as follows:

[0014] The mass fraction of polyvinyl pyrrolidone in water is 5 to 20 wt %, and the mass ratio of polytetrafluoroethylene dispersion to polyvinyl pyrrolidone is 0.5 to 4:1;

[0015] The stirring temperature is 30-70° C., and the stirring time is 5-24 hours.

[0016] Preferably, the electrospinning method in step (1) is specifically as follows: the propulsion speed is 0.2-1.5 mL / h, the spinning voltage is 13-22 kV, the receiving distance is 10-20 cm, the temperature is 20-40° C., and the humidity is 30-60%.

[0017] Preferably, the pre-oxidation temperature in step (1) is 200-300° C., the heating rate is 2-6° C. / min, and the holding time is 1-3 h.

[0018] Preferably, in step (1), the high temperature carbonization is carried out at a temperature of 600 to 1000° C., a heating rate of 2 to 6° C. / min, a holding time of 1 to 6 h, and an argon or nitrogen protective atmosphere.

[0019] Preferably, the molar ratio of 1,10-phenanthroline to copper acetate in the solution in step (2) is 5 to 30:1.

[0020] Preferably, the soaking time in the solution in step (2) is 5 to 60 minutes.

[0021] Preferably, the drying temperature in step (2) is 40 to 80° C., and the drying time is 12 to 48 hours.

[0022] Preferably, in step (2), the high temperature treatment is carried out at a temperature of 600 to 1000° C., a heating rate of 2 to 6° C. / min, a holding time of 1 to 6 h, and an argon or nitrogen protective atmosphere.

[0023] The third aspect of the present invention proposes an application of single-atom copper-doped porous carbon fiber in the negative electrode of a potassium metal battery, as follows:

[0024] The negative electrode of the potassium metal battery is a single-atom copper-doped porous carbon fiber / potassium composite negative electrode; the single-atom copper-doped porous carbon fiber is made into an anode, and potassium metal is made into a cathode. The anode and the cathode are immersed in a potassium ion electrolyte, and current is loaded at both poles to obtain the single-atom copper-doped porous carbon fiber / potassium composite negative electrode through an electrochemical deposition method.

[0025] Preferably, the single-atom copper-doped porous carbon fiber is cut into discs with a diameter of 8 to 16 mm as the anode, and the potassium metal is rolled into discs of the same size as the cathode.

[0026] Preferably, the anode and cathode are immersed in the potassium ion electrolyte, specifically, the two are assembled into a button battery in a glove box (water and oxygen content is less than 0.01 ppm).

[0027] Specifically, the potassium ion electrolyte contains KPF6 Or an electrolyte of KTFSI, wherein the concentration of potassium ions in the electrolyte is 0.8 to 4 M, and the organic solvent in the electrolyte is one or more of EC (ethylene carbonate), DEC (diethyl carbonate), EMC (ethyl methyl carbonate), DMC (dimethyl carbonate), and DME (ethylene glycol dimethyl ether).

[0028] Preferably, the current is 0.1-0.4 mA cm -2 ; The deposition time is 10 to 50 hours.

[0029] The fourth aspect of the present invention proposes an application of single-atom copper-doped porous carbon fiber in a potassium metal battery, wherein the potassium metal battery includes a single-atom copper-doped porous carbon fiber / potassium composite negative electrode, and the single-atom copper-doped porous carbon fiber / potassium composite negative electrode includes multiple single-atom copper-doped porous carbon fibers as a substrate and potassium metal deposited on the substrate.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The single-atom copper-doped porous carbon fiber of the present invention is a three-dimensional porous carbon material with high conductivity and large specific surface area. It can not only accommodate more potassium metal, but also buffer the volume change of potassium metal during the potassium plating / stripping process. At the same time, it can provide a conductive network, induce rapid charge transfer and reduce local current density, thereby slowing down the growth of dendrites.

[0032] (2) In the present invention, by introducing high-load single-atom copper, the material has maximum atomic utilization, tunable electronic structure and surface properties, can achieve low nucleation potential, improve the potassium affinity of carbon fiber, promote uniform electroplating of potassium metal, and thus improve the cycle stability of the battery. The single-atom copper-doped porous carbon fiber prepared by the present invention is used for the first time in a potassium metal battery, showing a cycle life of more than 400 hours.

[0033] (3) The present invention uses polyvinyl pyrrolidone (PVP), polytetrafluoroethylene dispersion (PTFE), and water as raw materials to prepare porous carbon fibers through electrospinning and carbonization, and then immerses the porous carbon fibers in an ethanol solution of 1,10-phenanthroline and copper acetate and sintering at high temperature to obtain single-atom copper-doped porous carbon fibers. The preparation method is simple and controllable, low in cost, and the raw materials are readily available, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope (SEM) image of the single-atom copper-doped porous carbon fiber in Example 1 of the present invention;

[0035] Figure 2is an X-ray diffraction (XRD) diagram of the single-atom copper-doped porous carbon fiber in Example 1 of the present invention;

[0036] Figure 3 This is a scanning transmission electron microscope (STEM) image of the single-atom copper-doped porous carbon fiber in Example 1 of the present invention;

[0037] Figure 4 This is a cycle performance diagram of a single-atom copper-doped porous carbon fiber / potassium composite negative electrode symmetrical battery in Example 1 of the present invention;

[0038] Figure 5 This is a cycle performance diagram of the porous carbon fiber / potassium composite negative electrode symmetrical battery in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Embodiment 1:

[0041] Preparation method of single-atom copper-doped porous carbon fiber:

[0042] (1) 1.0 g of PVP was added to 9 mL of water and stirred at 60 °C for 6 h. Subsequently, 1.8 g of PTFE was added and stirred for 12 h to obtain a uniform and stable precursor solution.

[0043] (2) 10 mL of the precursor solution was taken for electrospinning at a propulsion speed of 0.8 mL / h, a spinning voltage of 16 kV, a receiving distance of 18 cm, a temperature of 25° C., and a humidity of 50% to obtain a fiber membrane.

[0044] (3) The obtained fiber membrane was pre-oxidized at 260°C in air for 2 h, with a heating rate of 2°C / min. After pre-oxidation, it was carbonized at 800°C in a nitrogen atmosphere in a tubular furnace for 3 h, with a heating rate of 3°C / min, to obtain porous carbon fibers.

[0045] (4) The porous carbon fiber was immersed in 10 mL of ethanol solution containing 3.9 g of 1,10-phenanthroline and 0.18 g of copper acetate for 10 min, then taken out and dried at 60 ° C in a vacuum oven for 24 h. Subsequently, the porous carbon fiber was heated at 800 ° C for 2 h in a nitrogen atmosphere in a tubular furnace at a heating rate of 5 ° C / min to obtain a single-atom copper-doped porous carbon fiber.

[0046] The scanning electron microscope (SEM) image of the single-atom copper-doped porous carbon fiber is shown in Figure 2. Figure 1 As shown in the figure, it can be seen that carbon fiber has a rich pore structure. X-ray diffraction (XRD) is used to test the material. Figure 2 It can be seen that there is no diffraction peak of copper, indicating that copper exists in the form of single atoms. The material was characterized by scanning transmission electron microscopy (STEM). Figure 3 It can be seen that single-atom copper is evenly dispersed on the carbon fiber.

[0047] The application of single-atom copper-doped porous carbon fibers in the negative electrode of potassium metal batteries is as follows:

[0048] The prepared single-atom copper-doped porous carbon fiber was cut into a 12 mm diameter disc as the anode, and a 12 mm diameter potassium metal disc as the cathode. They were assembled into a button cell in a glove box (water and oxygen contents were both less than 0.01 ppm) for electrodeposition. The electrolyte was 3 M KTFSI dissolved in DME, and the constant current was 0.1 mA cm -2 After 40 hours of deposition, the single-atom copper-doped porous carbon fiber / potassium composite negative electrode was obtained. The single-atom copper-doped porous carbon fiber / potassium composite negative electrode was used as the counter electrode and working electrode of the button battery, the separator was glass fiber, and the electrolyte was 3M KFSI dissolved in DME to measure the cycle performance of potassium deposition / stripping.

[0049] Figure 4 The cycling performance of the single-atom copper-doped porous carbon fiber / potassium composite negative electrode symmetric battery is shown in Figure 2. At a current density of 0.5 mA cm -2 , with a surface capacity of 0.5 mAh cm -2 It has excellent performance and can circulate stably for 460 hours.

[0050] Embodiment 2:

[0051] The difference from Example 1 is that the preparation method of single-atom copper-doped porous carbon fiber is:

[0052] (1) 1.5 g of PVP was added to 8 mL of water and stirred at 50 °C for 12 h. Subsequently, 3.2 g of PTFE was added and stirred for 18 h to obtain a uniform and stable precursor solution.

[0053] (2) 8 mL of the precursor solution was taken for electrospinning at a propulsion speed of 0.6 mL / h, a spinning voltage of 18 kV, a receiving distance of 16 cm, a temperature of 25° C., and a humidity of 40% to obtain a fiber membrane.

[0054] (3) The obtained fiber membrane was pre-oxidized at 280°C in air for 2 h, with a heating rate of 5°C / min. After pre-oxidation, it was carbonized at 700°C in a nitrogen atmosphere in a tubular furnace for 2 h, with a heating rate of 2°C / min, to obtain porous carbon fibers.

[0055] (4) The porous carbon fiber was immersed in 10 mL of ethanol solution containing 4.3 g of 1,10-phenanthroline and 0.15 g of copper acetate for 20 min, then taken out and dried at 70 °C in a vacuum oven for 20 h. Subsequently, the porous carbon fiber was heated at 700 °C for 3 h in a nitrogen atmosphere in a tubular furnace at a heating rate of 3 °C / min to obtain a single-atom copper-doped porous carbon fiber.

[0056] Embodiment 3:

[0057] The difference from Example 1 is that the preparation method of single-atom copper-doped porous carbon fiber is:

[0058] (1) 0.8 g of PVP was added to 10 mL of water and stirred at 70 °C for 5 h. Subsequently, 2.5 g of PTFE was added and stirred for 10 h to obtain a uniform and stable precursor solution.

[0059] (2) 7 mL of the precursor solution was taken for electrospinning at a propulsion speed of 0.9 mL / h, a spinning voltage of 20 kV, a receiving distance of 15 cm, a temperature of 25° C., and a humidity of 45% to obtain a fiber membrane.

[0060] (3) The obtained fiber membrane was pre-oxidized at 230°C in air for 4 h, with a heating rate of 3°C / min. After pre-oxidation, it was carbonized at 900°C in a nitrogen atmosphere in a tubular furnace for 6 h, with a heating rate of 5°C / min, to obtain porous carbon fibers.

[0061] (4) The porous carbon fiber was immersed in 12 mL of ethanol solution containing 5.4 g of 1,10-phenanthroline and 0.12 g of copper acetate for 15 min, then taken out and dried at 80 °C in a vacuum oven for 18 h. Subsequently, the porous carbon fiber was heated at 900 °C for 2 h in a nitrogen atmosphere in a tubular furnace at a heating rate of 4 °C / min to obtain a single-atom copper-doped porous carbon fiber.

[0062] Comparative Example 1:

[0063] The steps and parameters are similar to those of Example 1, except that there is no subsequent immersion treatment in 1,10-phenanthroline and copper acetate solution.

[0064] The porous carbon fiber prepared in Comparative Example 1 was cut into a 12 mm diameter disc as the anode, and a 12 mm diameter potassium metal disc as the cathode. They were assembled into a button cell in a glove box (water and oxygen contents were both less than 0.01 ppm) for electrodeposition. The electrolyte was 3 M KTFSI dissolved in DME, and the constant current was 0.1 mA cm -2 After 40 hours of deposition, the porous carbon fiber / potassium composite negative electrode was obtained. The porous carbon fiber / potassium composite negative electrode was used as the counter electrode and working electrode of the button battery, the separator was glass fiber, and the electrolyte was 3M KFSI dissolved in DME to measure the cycle performance of potassium deposition / stripping.

[0065] Figure 5 The cycling performance diagram of the porous carbon fiber / potassium composite negative electrode symmetric battery. At a current density of 0.5 mA cm -2 , with a surface capacity of 0.5 mAh cm -2 The short circuit occurred after only 240 h of stable cycling, indicating severe dendrite growth.

[0066] In summary, the present invention prepares single-atom copper-doped porous carbon fibers through Examples 1-3, and the content of single-atom copper in the porous carbon fibers is 0.5wt% to 10.0wt%, the pore diameter on the porous carbon fibers is 100 to 600nm, and the specific surface area is 1000 to 3500m 2 g -1 .

[0067] The single-atom copper-doped porous carbon fiber / potassium composite negative electrode symmetrical battery prepared in Example 1 is compared with the porous carbon fiber / potassium composite negative electrode symmetrical battery in Comparative Example 1. It can be proved that the single-atom copper-doped porous carbon fiber prepared in the present invention can effectively inhibit dendrite growth and improve cycle stability, which has a good guiding significance in the application of potassium metal battery negative electrode. This method is conducive to the large-scale application of dendrite-free potassium metal negative electrode.

[0068] The above description is only used to help understand the method of the present invention and its core essence, but the protection scope of the present invention is not limited thereto. For those skilled in the art in the art, equivalent replacement or change according to the technical solution and inventive concept of the present invention within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. Single-atom copper-doped porous carbon fiber, characterized in that: The porous carbon fiber has a three-dimensional porous structure with a pore diameter of 100 to 600 nm and a specific surface area of ​​1000 to 3500 m 2 g -1 ; The surface of the porous carbon fiber is doped with uniformly dispersed single-atom copper, and the content of the single-atom copper is 0.5wt% to 10.0wt%.

2. A method for preparing single-atom copper-doped porous carbon fiber as claimed in claim 1, characterized in that: The following steps are involved: (1) Preparing porous carbon fibers: adding polyvinyl pyrrolidone and polytetrafluoroethylene dispersion into water and stirring to form a precursor solution, preparing a fiber membrane from the precursor solution by electrospinning, and then pre-oxidizing and high-temperature carbonizing the fiber membrane to obtain porous carbon fibers; (2) Preparation of single-atom copper-doped porous carbon fibers: The porous carbon fibers are immersed in a solution containing 1,10-phenanthroline and copper acetate and then dried, and then treated at high temperature to obtain single-atom copper-doped porous carbon fibers.

3. The method for preparing single-atom copper-doped porous carbon fiber according to claim 2, characterized in that: In step (1), a precursor solution is formed as follows: The mass fraction of polyvinyl pyrrolidone in water is 5 to 20 wt %, and the mass ratio of polytetrafluoroethylene dispersion to polyvinyl pyrrolidone is 0.5 to 4:1; The stirring temperature is 30-70° C., and the stirring time is 5-24 hours.

4. The method for preparing single-atom copper-doped porous carbon fiber according to claim 2, characterized in that: In step (1), the pre-oxidation temperature is 200-300° C., the heating rate is 2-6° C. / min, and the insulation time is 1-3 h.

5. The method for preparing single-atom copper-doped porous carbon fiber according to claim 4, characterized in that: In the step (1) of high temperature carbonization or the step (2) of high temperature treatment, the temperature is 600-1000° C., the heating rate is 2-6° C. / min, the holding time is 1-6 h, and the protective atmosphere is argon or nitrogen.

6. The method for preparing single-atom copper-doped porous carbon fiber according to claim 2, characterized in that: In step (2), the molar ratio of 1,10-phenanthroline to copper acetate in the solution is 5 to 30:

1.

7. The method for preparing single-atom copper-doped porous carbon fiber according to claim 2, characterized in that: The soaking time in the solution in step (2) is 5 to 60 minutes.

8. The method for preparing single-atom copper-doped porous carbon fiber according to claim 2, characterized in that: The drying temperature in step (2) is 40 to 80° C. and the drying time is 12 to 48 hours.

9. Application of single-atom copper-doped porous carbon fiber prepared by the preparation method according to any one of claims 2 to 8 in a potassium metal battery, characterized in that: The potassium metal battery comprises a single-atom copper-doped porous carbon fiber / potassium composite negative electrode, and the single-atom copper-doped porous carbon fiber / potassium composite negative electrode comprises multiple single-atom copper-doped porous carbon fibers as a substrate and potassium metal deposited on the substrate.

Citation Information

Patent Citations

  • Porous carbon fiber electrode for flow battery and preparation method of porous carbon fiber electrode

    CN112342689A

  • Nitrogen-doped porous carbon nanofiber sodium ion battery negative electrode material and preparation method thereof

    CN114361450A

  • Monatomic catalyst-loaded porous carbon fiber material as well as preparation method and application thereof

    CN115939408A

  • Nitrogen-sulfur co-doped porous carbon nanofiber-loaded PtCu alloy particle as well as preparation method and application thereof

    CN117219794A

  • Preparation method and application of Co and Cu co-doped CN-based composite material

    CN117680183A